Modes of Remembering in the Contemporary Spanish Novel. (August 2016) - Hansen, Hans Lauge
Abstract : This article examines the way in which the topic of civil war and Francoist repression has been narrated and understood in the contemporary Spanish novel after the turn of the millennium. The boom in what the article calls 'the affiliative memory novel' has been intimately related to the activities conducted by popular movements dedicated to the so‐called recuperation of the historical memory, but whether and to what extent is it possible to describe the phenomenon at hand as a coherent sub‐genre? It is a hypothesis that the way in which the relation between past, present and future is imagined in the text is, at least to some extent, related to the narrative form in which the novels are told, and by combining two paradigms of modal description, one narrative and the other ethico‐political, the article proposes eight different modes of remembering, among which three are considered more typical or generic. Finally, these three modes, the essentializing, the reconciliatory and the metamodernist modes, are examined and discussed within a transnational perspective.